A phenanthrene[9, 10-d]imidazole-phenol-based fluorescent probe combining ESIPT and AIE for the "turn-on" detection of Cu2+ with green-emission and improved Stokes' shift, and its application. (5th August 2021) - Du, Jiahui; Zhao, Bing; Kan, Wei; Yin, Haochun; Song, Tianshu; Wang, Liyan; Sun, Li; Wang, Xiuwen; Yin, Guangming; Wang, Jianxin
Abstract : The "turn-on" probe PIA(OH)-Py responds to Cu 2+ in living cells and can determine the concentration of Cu 2+ in blood samples. Abstract : The development of highly sensitive and selective fluorescent sensors toward Cu 2+ has gained considerable attention in view of its application of environmental and biological fields. However, the strategy of sensing by the fluorescence "turn-on" mode at a longer wavelength has not been well explored until now. In the present study, we report a novel green-emitting Cu 2+ -targeted fluorescent sensor, PIA(OH)-Py, with an improved Stokes' shift (182 nm), synergistically operated by the multi-mechanism based on the excited state intramolecular proton transfer (ESIPT) process combined with the aggregation-induced emission (AIE) phenomenon. A moderate fluorescence of PIA(OH)-Py was first fabricated with the effect of ESIPT-on as well as AIE-on. In the presence of Cu 2+, the strong emission of the in situ complex PIA(OH)-Py –Cu 2+ was obtained by the impact of further AIE-on accompanied by ESIPT-off as a fluorescence "turn on" response. In addition, the chelation-enhanced fluorescence (CHEF) mechanism was also partly responsible for the fluorescence increment due to the formation of the complex PIA(OH)-Py –Cu 2+ . Further study revealed that PIA(OH)-Py could respond to Cu 2+ in living cells by the green light channel and determine the concentration of Cu 2+ in real blood samples.